Pendampingan Optimalisasi Media Sosial untuk Meningkatkan Penjualan UMKM Kuliner di Kabupaten Demak - Abdullah Abdullah; Tri Sumiyanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The development of digital technology requires MSMEs to adapt to marketing their products online, particularly through social media. However, culinary MSMEs in Demak Regency still face limitations in managing social media effectively. This community service activity aims to improve the ability of culinary MSMEs to utilize social media as a digital marketing tool. The activity methods include training, intensive mentoring, content creation, and social media performance evaluation. The results of the activity show significant improvements in account management, content quality, follower interaction, and sales. This community service program demonstrates that social media mentoring can increase the competitiveness of culinary MSMEs in the digital era.